Differences in the distribution of risk factors for stroke among the high‐risk population in urban and rural areas of Eastern China. Issue 5 (7th April 2016) - Mi, Te; Sun, Shangwen; Du, Yifeng; Guo, Shougang; Cong, Lin; Cao, Mingfeng; Sun, Qinjian; Sun, Yi; Qu, Chuanqiang
Abstract: Introduction: Considering the program of screening for risk factors of stroke in Eastern China, the aim of this study was to compare the distribution differences in risk factors for stroke among the high‐risk population living in urban and rural areas. Methods: A total of 231, 289 residents were screened and basic information collected. Risk factors for stroke among the high‐risk population were compared between the urban and rural groups. Results: A total of 117, 776 high‐risk residents from urban areas and 113, 513 from rural areas were included in the analysis. The prevalence of hypertension was much higher in rural areas (73.3%) than that in urban areas (64.1%). Dyslipidemia (48.9% vs. 26.9%), sport lack (46.6% vs. 31.6%), diabetes mellitus (21.3% vs. 16.5%), and atrial fibrillation (18.7% vs. 9.8%) were more prevalent in the urban group, while smoking (26.5% vs. 28.8%), previous stroke (10.1% vs. 16.9%), and transient ischemic attack (20.9% vs. 24.6%) were less prevalent. Conclusion: Among the population at high risk of stroke, there were significant differences in the distribution of the following risk factors between the urban and rural groups: hypertension, atrial fibrillation, dyslipidemia, lack of physical exercise, and a previous stroke. Abstract : As the Chinese lifestyle has changed rapidly with the growth of economy and society during the past 3 decades, the incidence of risk factors for stroke in China has become similar to that in the Western countries. Hypertension, diabetes, hypercholesterolemia, smoking, atrial fibrillation, physical inactivity, obesity, and stroke family history are the major stroke factors for risk assessment. The objective of this study was to find out distribution differences in stroke risk factors between the urban and rural areas among high‐risk population in eastern China and thus to provide further direction of stroke management and prevention for high‐risk population.